Anthocyanin actions at the gastrointestinal tract: Relevance to their health benefits - Oteiza, Patricia I. (2022)
Anthocyanins (AC) are flavonoids abundant in the human diet, which consumption has been associated to several health benefits, including the mitigation of cardiovascular disease, type 2 diabetes, non-alcoholic fatty liver disease, and neurological disorders. It is widely recognized that the gastrointestinal (GI) tract is not only central for food digestion but actively participates in the regulation of whole body physiology. Given that AC, and their metabolites reach high concentrations in the intestinal lumen after food consumption, their biological actions at the GI tract can in part explain their proposed local and systemic health benefits. In terms of mechanisms of action, AC have been found to: i) inhibit GI luminal enzymes that participate in the absorption of lipids and carbohydrates; ii) preserve intestinal barrier integrity and prevent endotoxemia, inflammation and oxidative stress; iii) sustain goblet cell number, immunological functions, and mucus production; iv) promote a healthy microbiota; v) be metabolized by the microbiota to AC metabolites which will be absorbed and have systemic effects; and vi) modulate the metabolism of GI-generated hormones. This review will summarize and discuss the latest information on AC actions at the GI tract and their relationship to overall health benefits.